2016
DOI: 10.1016/j.triboint.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of mean wear coefficient during gear tests under various operating conditions

Abstract: a b s t r a c tSeven wear tests were conducted on an FZG gear testing machine in order to ascertain the influence of basestock (PAO and mineral), specific film thickness and contact load on the wear of spur gears, particularly on the wear coefficient κ that is used in Archard's law. The results showed that load may have some influence on the wear coefficient. They also showed that the influence of specific film thickness on wear is very non-linear. The influence of basestock, even with oils of similar viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A plethora of studies and experiments are carried out on wear occurring on gear wheels. Some of these studies are as follows: gear wear fault mechanism, most conventional researches mainly concentrated on the evaluation of gear wear [3][4][5][6][7][8][9], and the effect of gear wear on tooth profile [10], transmission errors [11,12] and mesh stiffness [13][14][15][16]. According to the mechanism of wear fault, dynamic study of tooth wear mainly focused on dynamic responses [14,17,18], and nonlinear dynamics [19].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies and experiments are carried out on wear occurring on gear wheels. Some of these studies are as follows: gear wear fault mechanism, most conventional researches mainly concentrated on the evaluation of gear wear [3][4][5][6][7][8][9], and the effect of gear wear on tooth profile [10], transmission errors [11,12] and mesh stiffness [13][14][15][16]. According to the mechanism of wear fault, dynamic study of tooth wear mainly focused on dynamic responses [14,17,18], and nonlinear dynamics [19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many scholars have researched the mechanism of wear failure, including the friction and wear mechanism of the medium belt [1], theoretical and experimental investigations into the teeth wear of spur gears of heavy-duty machinery [2], measurement of the mean wear coefficient [3], theoretical study of wear in internal gears [4], prediction of the steady-state wear rate [5], and the wear characteristics, surface finish, and microgeometry [6].…”
Section: Introductionmentioning
confidence: 99%
“…10 An increase in contact load also leads to an increase in wear and the wear behavior is non-linear at very low film thickness. 11…”
Section: Introductionmentioning
confidence: 99%
“…1,7 Power loss tests were performed on the FZG test rig, using carburized and high-pressure nitride steel gears for two different lubricants by Martins et al 8 The test results showed that wear in the nitride gear was higher with both lubricants than that of carburized gear. Some authors [9][10][11] have developed a wear model to quantify the effects of surface roughness, specific film thickness and contact load on accumulated wear depth in gear contact surfaces. The surface topography caused by manufacturing methods has a large influence on real contact area in the early life of the gear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation